Brand Loyalty in the Age of Consumer Empowerment: Building Sustainable Relationships Through Value Co-creation - Sucidha, Irma (Penelitian dan Pengembangan Ilmu, 2024)
In an era of consumer empowerment marked by technological advances and changes in consumer behavior, understanding the role of consumer collaboration in the co-creation process of brand loyalty is crucial for business success. Although the importance of brand loyalty has been recognized, there remains a lack of understanding of how consumer collaboration specifically influences brand loyalty, especially in today's dynamic context. This research aims to investigate the role of consumer collaboration in the co-creation process on brand loyalty in the era of consumer empowerment. By utilizing the systematic literature review method, relevant articles from reputable international databases, such as Scopus and Web of Science, were collected and analyzed. Findings from the literature review indicate that consumer collaboration in co-creation plays an important role in influencing brand loyalty by building trust, satisfaction, and emotional connection between brands and consumers. The practical implication of this research is that brands should prioritize consumer involvement in co-creation initiatives to increase brand loyalty and competitiveness in the market. Future studies could expand understanding of the relationship between consumers and brands and the effectiveness of co-creation strategies in increasing brand loyalty.